The Chinese Pinyin System Scheme-An Effective Tool for International Chinese Language Teaching (e-Journal of Linguistics, 2023)
As a tool for legal spelling and phonetic transcription of Chinese, theChinese Pinyin System Scheme is an indispensable tool forinternational Chinese teaching. International Chinese teachers shouldsystematically understand it in theory, pay attention to some details inthe teaching of Chinese Phonetic Alphabet, improve the teaching effectof Chinese Phonetic Alphabet, and avoid detours.
Keywords: The Chinese Pinyin System Scheme; International Chinese Teaching; Uses; Pinyin Teaching